Preparation and Characteristics of Expandable Graphite with Sodium Tripolyphosphate Assistant Intercalation - Zhai, Zhixiao; Pang, Xiuyan; Lin, Ruinian; Sun, Suyan; Weng, Mengqi (Asian Journal of Chemistry, 2015)
Expandable graphite having low initial expansion temperature and high dilatability was successfully prepared in graphite chemical oxidation and intercalating reaction with KMnO4 as an oxidant, H2SO4 as an intercalator and sodium tripolyphosphate (STPP) as an assistant intercalator. The mass ratio of C:KMnO4:H2SO4 (98 %):STTP was controlled as 1.0:0.18:5.0:0.7, H2SO4 diluted to 80 wt. % before intercalation reaction, and the reaction lasted 40 min at 40 °C. Expanded volume and initial expansion temperature of the prepared expandable graphite reached 630 mL/g (at 800 °C) and 146 °C, respectively. X-ray diffraction spectroscopy testified the intercalation and layer structure of expandable graphite, and Fourier transform infrared spectroscopy illuminated components of intercalating composite. Flame retardancy of expandable graphite for linear low density polyethylene was also investigated. Addition of 30 wt. % the expandable graphite to the polymer improved the limiting oxygen index from 17.5 to 28.4 %. On the other hand, the limiting oxygen index of the same amount of blank expandable graphite (with only H2SO4 as intercalator) was only 25.6 %. Assistant intercalation of sodium tripolyphosphate improved the dilatability and flame retardancy.